2017
DOI: 10.1002/mawe.201600766
|View full text |Cite
|
Sign up to set email alerts
|

Effect of praseodymium and erbium additions on solidification characteristics, microstructure and mechanical properties of as–cast ZRE1 magnesium alloy

Abstract: In this research, computer‐aided cooling curve thermal analysis, microstructure analysis, hardness measurements, and tensile test were performed to investigate the effect of praseodymium (Pr) and erbium (Er) additions on as‐cast ZRE1 magnesium (Mg) alloys. Results from the cooling curve and microstructure analysis showed that praseodymium and erbium altered the grain size of the alloys. Thermal analysis result demonstrated an increased solidification rate with praseodymium and erbium additions. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The results showed that the Mg-Zn-RE phase of base alloy was formed at 526.8 °C and With addition of 0.25 wt.% Er, the T Eu Mg-Zn-RE temperature of Mg-Zn-RE phase decreased by 0.8 °C. The smaller magnitude of this effect compared with that of the previous addition may be due to the Er content in the intermetallic secondary phase [9].…”
Section: Cooling Curves Analysismentioning
confidence: 78%
See 3 more Smart Citations
“…The results showed that the Mg-Zn-RE phase of base alloy was formed at 526.8 °C and With addition of 0.25 wt.% Er, the T Eu Mg-Zn-RE temperature of Mg-Zn-RE phase decreased by 0.8 °C. The smaller magnitude of this effect compared with that of the previous addition may be due to the Er content in the intermetallic secondary phase [9].…”
Section: Cooling Curves Analysismentioning
confidence: 78%
“…The experimental results showed that when 0.25 wt.% Er is added, the nucleation temperature of α-Mg phase decreases, which obtained at 643.8 °C. It is reported that the addition of erbium into Mg-Zn alloys facilitated the formation of the α-Mg phase at around 638°C, and this phase appeared as the first peak, which corresponded to the solidification of the magnesium matrix [9,14].…”
Section: Cooling Curves Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…This method is usually used during cooling or heating, especially solidification or melting. The most common techniques are Differential scanning calorimetry, Differential thermal analysis, thermogravimetric analysis, and cooling curve thermal analysis [9–11]. To increase measurement accuracy, the size of samples must be big enough and solidify over long enough time.…”
Section: Introductionmentioning
confidence: 99%